2019
DOI: 10.1111/gwat.12946
|View full text |Cite
|
Sign up to set email alerts
|

Joint Estimation of Gross Recharge, Groundwater Usage, and Hydraulic Properties within HydroSight

Abstract: Groundwater management decisions are often founded upon estimates of aquifer hydraulic properties, recharge and the rate of groundwater usage. Too often hydraulic properties are unavailable, recharge estimates are very uncertain, and usage is unmetered or infrequently metered over only recent years or estimated using numerical groundwater models decoupled from the drivers of drawdown. This paper extends the HydroSight groundwater time‐series package ( http://peterson-tim-j.github.io/HydroSight/) to allow the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Recognizing the importance of evaporation in their model setup, they constrained the parameter estimation by including the correct simulation of the seasonal behavior in the objective function. Peterson and Fulton (2019) used a nonlinear TFN model that includes a soil moisture module to estimate recharge (Peterson and Western, 2014). To obtain reasonable estimates of recharge, the model was constrained by comparing the modeled evaporation to the expected actual evaporation obtained using the Budyko curve.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the importance of evaporation in their model setup, they constrained the parameter estimation by including the correct simulation of the seasonal behavior in the objective function. Peterson and Fulton (2019) used a nonlinear TFN model that includes a soil moisture module to estimate recharge (Peterson and Western, 2014). To obtain reasonable estimates of recharge, the model was constrained by comparing the modeled evaporation to the expected actual evaporation obtained using the Budyko curve.…”
Section: Introductionmentioning
confidence: 99%
“…For annual recharge rates it was found that the non-linear model provides good estimates with relatively small deviations from the recharge measured with the lysimeters, while the linear models shows significantly larger deviations and a structural overestimation of annual recharge rates. The non-linear model also provided reasonable estimates for recharge summed over 10-day periods, suggesting that this model may be used to obtain recharge estimates at smaller time scales than reported so far (e.g., Obergfell et al, 2019;Peterson and Fulton, 2019). Using detailed information from the lysimeters present https://doi.org/10.5194/hess-2020-392 Preprint.…”
Section: Discussionmentioning
confidence: 71%
“…A response function that accounts for this could then be used (e.g., the four-parameter response function), but the estimated flux R should then be interpreted as drainage from the root zone to the groundwater and not as recharge occurring at the water table. Peterson and Fulton (2019) suggested that the flux could be "averaged over a period greater than the time lag" to provide an estimate of gross recharge in this case. This approach was applied here for the presentation of the annual recharge rates, where also the recharge estimates from the linear model were considered.…”
Section: Hydrogeological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Guided global search of the solution space using Shuffled Complex Evolution (SCE, ) resulting in a single model run with the highest error metric value achievable. Due to inherent randomness in search routines like SCE, it is a common practice to repeat the search multiple times (Peterson & Fulton, 2019;. Here, each modeling example was repeated 10 times for each error metric.…”
Section: Experiments Designmentioning
confidence: 99%